Penerapan Budidaya Ikan dalam Ember “Budikdamber” untuk Meningkatkan Ketahanan Pangan di Masa Pandemi Covid-19 di Desa Kalisari Kecamatan Rowokele Kabupaten Kebumen (Abdibaraya: Jurnal Pengabdian Masyarakat, 2022)
During this pandemic, many people have suffered from Covid-19 which has resulted in a decrease in family income. One way to strengthen household food security is by cultivating fish in buckets or commonly known as the Budidaya Ikan dalam Ember “Budikdamber” technique. This strategy does not require a large area and is easy for everyone to do. This is expected to be a solution to the problems experienced. This community service activity aims to provide information and skills for all elements of society that are formed in several groups, such as the PKK group, Rt/Rw, Muslim recitation group, and father recitation group in Kalisari village. The results obtained by the service partners from this service activity are that the catfish harvest is not carried out simultaneously for all buckets. Harvest catfish about 2-4 months of maintenance. While the kale harvest is done when the maintenance period is approximately 2-3 weeks with an average harvest of 1 bunch for 2 buckets. However, the next harvest is about 1-2 weeks with an average harvest of 1 bunch for 1 bucket. Keywords: Budikdamber, food security, economy, covid 19